2022
DOI: 10.3390/cancers14020290
|View full text |Cite
|
Sign up to set email alerts
|

Claudins and Gastric Cancer: An Overview

Abstract: Despite recent improvements in diagnostic ability and treatment strategies, advanced gastric cancer (GC) has a high frequency of recurrence and metastasis, with poor prognosis. To improve the treatment results of GC, the search for new treatment targets from proteins related to epithelial–mesenchymal transition (EMT) and cell–cell adhesion is currently being conducted. EMT plays an important role in cancer metastasis and is initiated by the loss of cell–cell adhesion, such as tight junctions (TJs), adherens ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 129 publications
(178 reference statements)
2
57
0
3
Order By: Relevance
“…EMT and gastric cancer stem cells underlie the development of metastasis in gastric cancer and are important causes of refractory and recurrent gastric cancer (37,51). Our study revealed that NPRL2 might regulate the malignant biological behaviour of gastric cancer by affecting the EMT regulators and stemness of cells, which was consistent with Ji et al's study in lung cancer (8), where NPRL2 was able to inhibit the growth and metastasis of cancer cells.…”
Section: Discussionsupporting
confidence: 91%
“…EMT and gastric cancer stem cells underlie the development of metastasis in gastric cancer and are important causes of refractory and recurrent gastric cancer (37,51). Our study revealed that NPRL2 might regulate the malignant biological behaviour of gastric cancer by affecting the EMT regulators and stemness of cells, which was consistent with Ji et al's study in lung cancer (8), where NPRL2 was able to inhibit the growth and metastasis of cancer cells.…”
Section: Discussionsupporting
confidence: 91%
“…RhoA signaling is crucial for two clinical aspects [ 5 , 38 , 39 ]: (1) possible biomarkers and (2) therapeutic target possibilities, based on the aforementioned functional roles of RHOA and our meta-analysis findings. Meta-analyses can provide insights for the usage of RHOA for patient classification.…”
Section: Discussionmentioning
confidence: 99%
“…CLDN18.2, an epithelial tight junction protein, is strictly confined to tight junctions in the gastric mucosa. However, in GC, perturbations in cell polarity lead to CLDN18.2 being exposed on the cancer cell surface and targetable by antibodies [ 28 , 29 ]. AMG 910, an antibody construct designed to engage CD3-positive T cells with CLDN18.2-expressing GC cells, whose anti-tumor effect for CLDN18.2-positive GC or gastroesophageal junction (GEJ) adenocarcinoma is now studied, is expected to be effective [ 30 ].…”
Section: Genomics For Diffuse-type Gastric Cancer and Possible Therap...mentioning
confidence: 99%